56.3k views
2 votes
-14-7(9v+3)=13v+41 ​

User Fhd
by
5.0k points

2 Answers

6 votes

Answer:

v = 12.67

95% sure... I could be wrong, though.

Explanation:

14-7(9v+3)=13v+41 ​

-14-63v-21=13v+41

-14-21=76v

6=76v

12.67=v

User Hiero
by
5.6k points
5 votes

Answer:

v=−1

Explanation:

Step 1: Simplify both sides of the equation.

−14−7(9v+3)=13v+41

−14+(−7)(9v)+(−7)(3)=13v+41(Distribute)

−14+−63v+−21=13v+41

(−63v)+(−14+−21)=13v+41(Combine Like Terms)

−63v+−35=13v+41

−63v−35=13v+41

Step 2: Subtract 13v from both sides.

−63v−35−13v=13v+41−13v

−76v−35=41

Step 3: Add 35 to both sides.

−76v−35+35=41+35

−76v=76

Step 4: Divide both sides by -76.

−76v

−76

=

76

−76

v=−1

User Trevor Gehman
by
5.4k points